Glyphosate resistance in kochia - Godar, Amar Singh (Kansas State University, 2013)
Kochia [Kochia scoparia (L.) Schrad.] is a weed of great economic importance in the Great Plains and western United States and Canada. This weed is prone to evolving resistance to herbicides. Glyphosate is the most widely used herbicide in glyphosate-resistant crops and chemical fallow, and is extremely valuable to crop production. Anecdotal reports of kochia control failure with glyphosate in western Kansas arose during the mid-2000’s. The objectives of this research were to (1) confirm and characterize glyphosate resistance in kochia and measure its impact in western Kansas, (2) gather information on grower weed management practices before and since glyphosate resistance in kochia was confirmed, and (3) determine if altered absorption and translocation of glyphosate contributes to glyphosate resistance in kochia. Dose-response studies on greenhouse and outdoor grown plants, and shikimate accumulation assays confirmed one kochia population collected in 2007 and eight populations collected in 2010 tolerated three- to eleven-times more glyphosate compared to a known glyphosate-susceptible (GS) population. Furthermore, 40 kochia populations collected in 2012 showed varied response, from slightly elevated tolerance to resistance to 0.84 kg ae ha-1 glyphosate. Further analysis suggested these populations were at different stages of resistance evolution. An online survey revealed that growers increased glyphosate use rate and application frequency, but decreased exclusive use of glyphosate and diversified weed management practices during post- compared to pre-glyphosate confirmation periods. Most survey respondents reported presence of glyphosate-resistant (GR) kochia in at least in few fields, and half reported GR kochia in a majority of fields. Thus, together with the resistance confirmation studies, it is estimated that at least one-third of western Kansas kochia populations have evolved resistance to glyphosate. Nominal differences in absorption and translocation of 14C-glyphosate observed between GS and GR kochia populations likely do not contribute to differential response of these populations to glyphosate. Glyphosate-resistant kochia has become widespread in western Kansas in a short period of time. Use of weed resistance best management practices (BMP) is imperative to sustain the utility of glyphosate in the region.
Keywords: Glyphosate; Kochia; Glyphosate resistance; Herbicide resistance; ED50; GR50; Agronomy (0285)